ENHANCING STUDENTS' ECOLITERACY IN UTILIZATION OF SCHOOL AREA THROUGH AQUAPONIC PROJECT AS LEARNING MODEL IN SOCIAL STUDIES LEARNING (CLASSROOM ACTION RESEARCH IN CLASS VII-B SMP PASUNDAN 2 BANDUNG) - Pramesthi, Herdyan Ratih (International Journal Pedagogy of Social Studies, 2017)
Abstract -Ecoliteracy comes as a solution to various environmental problems that occur. Understanding ecoliteracy should be introduced early, in order grow and development of every human being always has awareness to maintain the environment. Based on preliminary observations conducted by researchers in SMP Pasundan 2 Bandung in class VII-B, showed that the low Ecoliteracy of students, shown by the scattering of garbage in the classroom environment, students also never care for the classroom environment, school environment, or wilting plants around the school due to lack of care. Based on the observation, the researcher concludes that, it is necessary to increase the students’ ecoliteracy in the utilization of the school area. By looking at the problems occurring in class VII-B, the researcher intends to conduct classroom action research by applying the aquaponic learning model of the Social Studies learning. The research design used in this research is a Lewin cycle model according to Elliot. During the execution, this study was conducted 2 cycles, with 5 actions in each cycle consisting of an understanding of ecoliteracy, aquaponic project creation, aquaponic project maintenance, aquaponic harvesting process, accountability report, and harvesting of crops into healthy foods. Based on the results of students’ ecoliteracy research, in the utilization of school area on the cycle 1 results have shown an improvement, but the improvement is not maximal, with the average group assessment entered into the "Good" category. While in the cycle 2 experienced a significant improvement, making the percentage of group valuation to entered into the "Excellent" category. The conclusion of this research is the use of aquaponic learning model in Social Studies learning can  improve the students' ecoliteracy in the utilization of the school area. Keywords: students' ecoliteracy enhancement, aquaponic project, social studies learning